2018
DOI: 10.1038/s41598-018-30578-4
|View full text |Cite|
|
Sign up to set email alerts
|

Snake Venom Extracellular vesicles (SVEVs) reveal wide molecular and functional proteome diversity

Abstract: Proteins constitute almost 95% of snake venom’s dry weight and are produced and released by venom glands in a solubilized form during a snake bite. These proteins are responsible for inducing several pharmacological effects aiming to immobilize and initiate the pre-digestion of the prey. This study shows that proteins can be secreted and confined in snake venom extracellular vesicles (SVEVs) presenting a size distribution between 50 nm and 500 nm. SVEVs isolated from lyophilized venoms collected from four diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 118 publications
(143 reference statements)
2
23
0
Order By: Relevance
“…The size distribution of SVEVs was found to be between approximately 50–500 nm. Proteomic investigations revealed that SVEVs could be assigned to eight different protein classes, such as SVMP, SVSP, and disintegrins [ 135 ].…”
Section: Discussionmentioning
confidence: 99%
“…The size distribution of SVEVs was found to be between approximately 50–500 nm. Proteomic investigations revealed that SVEVs could be assigned to eight different protein classes, such as SVMP, SVSP, and disintegrins [ 135 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other components include carbohydrates, lipids, metal ions, and inorganic anions. The most common enzymes include phospholipase A2 (PLA2), hyaluronidase, metalloproteases, l -amino acid oxidase ( l -AAO), acetylcholinesterases, and serine proteases [ 10 ].…”
Section: Snake Venom: An Overviewmentioning
confidence: 99%
“…However, the EVs reported in the venom of venomous animals are known by different names, including microvesicles ( Crotalus durissus terrificus ) [ 16 ], exosome-like vesicles ( Gloydius blomhoffi blomhoffi ) [ 17 ], small membranous vesicles ( Gloydius blomhoffi blomhoffi ) [ 18 ], mixed-strategy extracellular vesicles ( Leptopilina heterotoma ) [ 19 ], venosomes ( Leptopilina heterotoma and Leptopilina boulardi ) [ 20 ], and extracellular vesicles ( Leptopilina heterotoma ) [ 21 ]. The functional molecules in the EVs of snake ( Agkistrodon contortrix ) venom are primarily virulence-related proteins, with significant cytotoxic activity [ 22 ]. Parasitoid wasp venom EVs contain immunosuppressive proteins that can target and kill the Drosophila’s lamellocyte, increasing the success of wasp parasitism on certain Drosophila species [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%